Advances in methods for evaluating anti-wrinkle efficacy in the periocular and perioral areas - TAN Huiling; LV Hua; WEN Si; YE Li; LIU Zhenfeng (Pifu-xingbing zhenliaoxue zazhi)
The evaluation of anti-wrinkle efficacy in the periocular and perioral areas is a key area of cosmetic research and development and clinical medicine. In recent years, with breakthroughs in emerging technologies such as artificial intelligence, multispectral imaging, and two-photon microscopy, evaluation methods have gradually shifted from traditional subjective assessments to multidimensional, high-precision objective quantitative analysis. This paper systematically reviews the research progress of subjective assessment methods and objective analysis methods (such as 3D skin detection, dynamic facial expression capture, biomarker detection), focusing on the innovative application of AI algorithms in wrinkle classification and quantification, as well as the potential of the integration of multimodal technologies (such as AI+3D imaging+biomechanical testing) to enhance the reliability of the evaluation. The paper also highlights the limitations of the current research, including the lack of standardization of subjective evaluation, the lack of uniform standards for dynamic wrinkle assessment, and the absence of a population-specific evaluation system for Chinese individuals. It proposes future directions for technological development, such as real-time monitoring of dynamic wrinkles, establishment of multimodal evaluation models, and optimization of detection instruments tailored to Asian skin.